Extracorporeal Cardiac Shock Wave-Induced Exosome Derived From Endothelial Colony-Forming Cells Carrying miR-140-3p Alleviate Cardiomyocyte Hypoxia/Reoxygenation Injury via the PTEN/PI3K/AKT Pathway - Yang, Dan; Wang, Mingqiang; Hu, Zhao; Ma, Yiming; Shi, Yunke; Cao, Xingyu; Guo, Tao; Cai, Hongbo; Cai, Hongyan (Frontiers in Cell and Developmental Biology, 2022)
Background: Stem cell-derived exosomes have great potential in the treatment of myocardial ischemia-reperfusion injury (IRI). Extracorporeal cardiac shock waves (ECSW) as effective therapy, in part, could activate the function of exosomes. In this study we explored the effect of ECSW-induced exosome derived from endothelial colony-forming cells on cardiomyocytes hypoxia/reoxygenation (H/R) injury and its underlying mechanisms. Methods: The exosomes were extracted and purified from the supernatant of endothelial colony-forming cells (ECFCs-exo). ECFCs-exo treated with shock wave (SW-exo) or without shock wave (CON-exo) were performed high-throughput sequencing of the miRNA. H9c2 cells were incubated with SW-exo or CON-exo after H/R injury. The cell viability, cell apoptosis, oxidative stress level and inflammatory factor were assessed. qRT-PCR was used to detect the expression levels of miRNA and mRNA in cells and exosomes. The PTEN/PI3K/AKT-pathway-related proteins were detected by western blotting, respectively. Results: Exosomes secreted by ECFCs could be taken up by H9c2 cells. Administration of SW-exo to H9c2 cells after H/R injury could significantly improve cell viability, inhibit cell apoptosis, and down-regulate oxidative stress level (P＜0.01), with an increase of Bcl-2 protein and a decrease of Bax, Cleaved caspase-3 and NF-κB protein (P＜0.05). Notably, miR-140-3p was found to be highly enriched both in ECFCs and ECFCs-exo treated with ECSW (P＜0.05) and served as a critical mediator. SW-exo increased miR-140-3p expression but decreased PTEN expression in H9c2 cells with enhanced phosphorylation of PI3K/AKT signaling pathway. These cardioprotective effects of SW-exo on H/R injury were blunted by miR-140-3p inhibitor. Dual-luciferase assay verified that miR-140-3p could directly target the 3'UTR of PTEN mRNA and exert a negative regulatory effect. Conclusion: This study has shown the potential of ECSW as an effective stimulation for the exosomes derived from ECFCs in vitro. SW-exo exerted a stronger therapeutic effect on H/R injury in H9c2 cells possibly via delivering exosomal miR-140-3p, which might be a novel promising strategy for the myocardial IRI.